Digital Marketing Strategy in Tourist Objects of Lerep Village, Ungaran, Semarang District - Nur Jannah, Desika; Arvianto, Bram (Universitas Pendidikan Ganesha, 2023)
The tourism industry in Semarang and authorities outside Semarang to advance the tourism industry villages by posting photos or recordings through onlinebased media. This post has a fairly large reach consisting of a wider area both inside and outside Semarang, progress through web-based media such as Facebook and Instagram, making the exchange of advertisements in the computerized era lead to a focus on the general public. As well as making the travel industry village develop as a whole, establishing POKDARWIS, advancing the travel industry through web-based media, building good relationships with supporting media, both print media, electronic media and online media.